Incentives in hierarchical organizations - Balashov, Vladimir; Burkov, Vladimir; Novikov, Dmitrij; Zalojnev, Aleksei (Journal of Business Economics and Management, 2003)
Game‐theoretical models of the incentive mechanisms are considered for the hierarchical organization.First Published Online: 14 Oct 2010